Survival rate of colorectal cancer in China: A systematic review and meta-analysis - Wang, Ren; Lian, Jie; Wang, Xin; Pang, Xiangyi; Xu, Benjie; Tang, Shuli; Shao, Jiayue; Lu, Haibo (Frontiers in Oncology, 2023)
Background: This study aims to comprehensively summarize the colorectal survival rate in China. Method: In PubMed and Web of Science, keywords such as "colorectal cancer", "survival" and "Chi-na" were used to search literatures in the past 10 years. Random effect models were selected to sum-marize 1-year, 3-year, and 5-year survival rates, and meta-regression and subgroup analyses were performed on the included studies. Results: A total of 16 retrospective and prospective studies providing survival rates for colorectal cancer in China were included. The 1-year, 3-year, and 5-year survival rates of colorectal cancer in China were 0.79 (95%CI: 0.63-0.94), 0.72 (95%CI: 0.64-0.79), 0.62 (95%CI: 0.54-0.70), respectively. Among them, the 5-year survival rate of colorectal cancer was 0.82 in Tianjin, 0.76 in Beijing, 0.71, 0.67, 0.66, 0.65 and 0.63 in Guangdong, Shandong, Liaoning, Zhejiang and Shanghai, respectively. In the included studies, the 5-year survival rates of stage I (5474 patients), stage II (9215 cases), stage III (8048 cases), and stage IV colorectal cancer patients (4199 cases) were 85%, 81%, 57%, and 30%, respectively. Conclusion: The 5-year survival rate in China is close to that of most European countries, but still lower than Japan and South Korea, and the gap is gradually narrowing. Region, stage, differentiation, pathological type, and surgical approach can affect 5-year survival in colorectal cancer.